HATERS di Instagram: Antara Meluapkan Kebencian dan Memeroleh Keuntungan (ETNOSIA : Jurnal Etnografi Indonesia, 2018)
News around celebrity’s life has been the topic of interest of televition audience and netizens, and causes pros and cons. Those who pros claim to be the fans of the celebrity. On the contrary, those who cons refer themselves as haters. This article focuses on how haters express their hate through haters account in Instagram and how the owner of haters account earn money from their account, using two most popular celebrities who have the highest number of haters account in Indonesia, Mulan Jameela and Ayu Ting Ting. The study indicates that in spreading hatred of celebrities in Instagram, there are generally two categories of haters, the owner and the followers of haters account. In regard to their activities, followers of haters account can be divided into three: followers who only observe the uploads, followers who only ‘like’ the uploads through ‘love’ symbol, and followers who comment on the uploads. But, not all followers of haters account are haters. Whether or not one is a hater, this can be seen from one’s hatred comments. On the contrary, by solely observing or liking uploads one cannot be perceived as a non-hater. Passivity of followers to uploads can happen because of various reasons (i.e. using original identity, afraid of bullying from the lovers of hated celebrity). Haters account is not just a media to express their hate, but also a way to earn money for those who have lots of followers, by promoting online shop in their own haters account, called paid promote.
Keywords: Instagram; haters; followers; celebrity; and paid promote.